-3x(x+5)-7=-8+10

Simple and best practice solution for -3x(x+5)-7=-8+10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3x(x+5)-7=-8+10 equation:


Simplifying
-3x(x + 5) + -7 = -8 + 10

Reorder the terms:
-3x(5 + x) + -7 = -8 + 10
(5 * -3x + x * -3x) + -7 = -8 + 10
(-15x + -3x2) + -7 = -8 + 10

Reorder the terms:
-7 + -15x + -3x2 = -8 + 10

Combine like terms: -8 + 10 = 2
-7 + -15x + -3x2 = 2

Solving
-7 + -15x + -3x2 = 2

Solving for variable 'x'.

Reorder the terms:
-7 + -2 + -15x + -3x2 = 2 + -2

Combine like terms: -7 + -2 = -9
-9 + -15x + -3x2 = 2 + -2

Combine like terms: 2 + -2 = 0
-9 + -15x + -3x2 = 0

Factor out the Greatest Common Factor (GCF), '-3'.
-3(3 + 5x + x2) = 0

Ignore the factor -3.

Subproblem 1

Set the factor '(3 + 5x + x2)' equal to zero and attempt to solve: Simplifying 3 + 5x + x2 = 0 Solving 3 + 5x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '-3' to each side of the equation. 3 + 5x + -3 + x2 = 0 + -3 Reorder the terms: 3 + -3 + 5x + x2 = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 5x + x2 = 0 + -3 5x + x2 = 0 + -3 Combine like terms: 0 + -3 = -3 5x + x2 = -3 The x term is 5x. Take half its coefficient (2.5). Square it (6.25) and add it to both sides. Add '6.25' to each side of the equation. 5x + 6.25 + x2 = -3 + 6.25 Reorder the terms: 6.25 + 5x + x2 = -3 + 6.25 Combine like terms: -3 + 6.25 = 3.25 6.25 + 5x + x2 = 3.25 Factor a perfect square on the left side: (x + 2.5)(x + 2.5) = 3.25 Calculate the square root of the right side: 1.802775638 Break this problem into two subproblems by setting (x + 2.5) equal to 1.802775638 and -1.802775638.

Subproblem 1

x + 2.5 = 1.802775638 Simplifying x + 2.5 = 1.802775638 Reorder the terms: 2.5 + x = 1.802775638 Solving 2.5 + x = 1.802775638 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2.5' to each side of the equation. 2.5 + -2.5 + x = 1.802775638 + -2.5 Combine like terms: 2.5 + -2.5 = 0.0 0.0 + x = 1.802775638 + -2.5 x = 1.802775638 + -2.5 Combine like terms: 1.802775638 + -2.5 = -0.697224362 x = -0.697224362 Simplifying x = -0.697224362

Subproblem 2

x + 2.5 = -1.802775638 Simplifying x + 2.5 = -1.802775638 Reorder the terms: 2.5 + x = -1.802775638 Solving 2.5 + x = -1.802775638 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2.5' to each side of the equation. 2.5 + -2.5 + x = -1.802775638 + -2.5 Combine like terms: 2.5 + -2.5 = 0.0 0.0 + x = -1.802775638 + -2.5 x = -1.802775638 + -2.5 Combine like terms: -1.802775638 + -2.5 = -4.302775638 x = -4.302775638 Simplifying x = -4.302775638

Solution

The solution to the problem is based on the solutions from the subproblems. x = {-0.697224362, -4.302775638}

Solution

x = {-0.697224362, -4.302775638}

See similar equations:

| 3a-(5-3a)=10 | | 4(q)+(-1)(1-q)=1q+2(1-q) | | 5x+-6=3x+-8 | | (3-x)+(x-4)=2(x+4) | | w=-125t+6000 | | -6+5(-9x-3)=-10 | | -6+(-9x-3)=-10 | | 24+r=28 | | 5p+8=-32 | | 2=-19+z | | 6m-4=4m | | 2=-4+k | | 18p^3-63p^2-9p=0 | | 4x^2+8x+48y-44=0 | | -7(2x-8)+3=-14x+59 | | 10-4=16 | | Q-3=25 | | F(x)=ln(x)*x^2 | | 66=10-8b | | K-12=11 | | b/2=-7 | | 4b+3a= | | 1-2r=9-r | | 12x^4-26x^3+10x^2=0 | | 9x-2=9(x+8) | | 8=6-p(p+3) | | 2x(6x^3-13x^2+5x)=0 | | 8y^3+6y^2-9y= | | 5(32n-40)=4(5n+1) | | x=2(1-x) | | p+12=-5 | | 22x+3x^2=-40 |

Equations solver categories